Hubungan antara Intensitas Penggunaan Media Sosial dan Self-Esteem pada Remaja SMA di Kota Jambi - Ary Setiani; Elinda Widya Septi. R; Mutia Aulia Syahputri; Beny Rahim; Jelpa Periantalo; Muhammad Ilham; Dinda Agraiza (INDO PUBLISHING, 2026)
This study aims to determine the relationship between the intensity of social media use and self-esteem among high school students in Jambi City. This study employs a quantitative approach using purposive sampling. The research subjects were 99 high school students in Jambi City who actively use social media. The instruments used were a social media usage intensity scale developed based on engagement, attention, duration, and frequency, as well as the Rosenberg Self-Esteem Scale (RSES), which has been adapted into Indonesian. Normality tests were conducted using the Shapiro-Wilk test, which indicated that the data were normally distributed for the social media usage intensity variable (SW = 0.984; p = 0.291) and the self-esteem variable (SW = 0.977; p = 0.086). Data analysis was performed using Pearson’s correlation, which indicated a significant negative relationship between the intensity of social media use and adolescents’ self-esteem (r = -0.261; p = 0.0009), with the strength of the relationship classified as weak. This means that the higher the intensity of social media use, the lower the self-esteem among adolescents. This study indicates a need for digital learning programs and psychological support to foster positive self-esteem development among adolescents who use social media.